2005
DOI: 10.1091/mbc.e04-06-0516
|View full text |Cite
|
Sign up to set email alerts
|

Staufen Recruitment into Stress Granules Does Not Affect Early mRNA Transport in Oligodendrocytes

Abstract: INTRODUCTIONFrom the early steps of mRNA transport to the latest events of degradation, cytoplasmic RNA granules are highly relevant to the physiology of mRNA, including silencing and activation (reviewed in Wickens and Goldstrohm, 2003). Granules packaging targeted mRNAs appear in oligodendrocytes and other polarized vertebrate cells as dense structures, containing also ribosomes and with an average diameter of 1 m ( Barbarese et al., 1995;Barry et al., 1996;Ainger et al., 1997;Knowles and Kosik, 1997;Carson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 74 publications
13
134
1
2
Order By: Relevance
“…The large granules that formed in the presence of puromycin were reminiscent of SGs. It has been reported that various cellular stresses, including puromycin treatment, induce the accumulation of a number of RNA-binding proteins such as Staufen (Thomas et al, 2005), FMRP (Mazroui et al, 2002), and elements of the translational machinery including PABP and eIF4E into SGs (Kedersha et al, 2005).…”
Section: Pum2 Is Found In Ribonucleoparticles and Is Recruited Into Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The large granules that formed in the presence of puromycin were reminiscent of SGs. It has been reported that various cellular stresses, including puromycin treatment, induce the accumulation of a number of RNA-binding proteins such as Staufen (Thomas et al, 2005), FMRP (Mazroui et al, 2002), and elements of the translational machinery including PABP and eIF4E into SGs (Kedersha et al, 2005).…”
Section: Pum2 Is Found In Ribonucleoparticles and Is Recruited Into Dmentioning
confidence: 99%
“…Recently, RNA-binding proteins such as fragile X mental retardation protein (FMRP), Staufen, and Smaug, which are involved in dendritic mRNA localization and translation, have been found to accumulate in stress granules (SGs) (Mazroui et al, 2002;Baez and Boccaccio, 2005;Thomas et al, 2005;Kim et al, 2006). This process occurs when cells are exposed to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Stress granules can be formed in response to heat shock (Mazroui et al, 2002), oxidative stress (Thomas et al, 2004), RNA binding protein over expression (Solomon et al, 2007), expression of a phosphomimetic mutant form of eukaryotic initiation factor 2 (eIF-2) (McEwen et al, 2005) and interfering with eIF4A activity (Mazroui et al, 2006). To determine whether the granules formed by expression of EGFP-FMRP were stress granules, rat pheochromocytoma cells (PC12) were transiently transfected with an EGFP-FMRP expression vector.…”
Section: Egfp-fmrp Expression and Stress Granule Markersmentioning
confidence: 99%
“…For presentation, granule size distributions were all normalized to 500 particles and the normalized distributions were compared using the Ftest for two sample variance. Protein co-localization measurements were performed by counting single-and double-stained granules of acquired images (Thomas et al, 2004). …”
Section: Image Analysesmentioning
confidence: 99%
“…These proteins finely control the successive steps that insure proper expression of mRNA at specific times and space. Staufen2 (Stau2), a protein mainly expressed in brain is a well accepted player for mRNA localization (4)(5)(6)(7)(8)(9). In brain, Stau2 is expressed in several cell types including neurons and oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%